ASSOCIATION BETWEEN FINGERPRINT PATTERNS AND MYOPIA - Sretić, Ljiljana (Bulletin of Natural Sciences Research, 2018)
Epidermal patterns are polygenically determined system of ridges on volar surface of fingers, palms and soles. Due to their mode of inheritance, and developmental time that coincide with the most critical period of embryogenesis, they are considered as a biological marker that may provide an insight in early fetal life. This study involved 102 participants, students from the University of Priština-Kosovska Mitrovica, 51 consisting myopic and 51 control group. Analysis of fingerprint patterns has showed significantly altered dermatoglyphic configuration of arch patterns in myopic group, which might be suggestive of developmental perturbances in embryogenesis of genetically vulnerable individuals prone to development of myopia.
Keywords: Epidermal patterns; Myopia; Arches